Resolusi Konflik Sosial dalam Hukum Keluarga Islam : Perspektif Sosiologi dan Antropologi - Huzaini Huzaini; Rachmat Panca Putera (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
This study examines social conflicts in Islamic family law (HKI) using sociological and anthropological approaches to understand the complex dynamics between religion, culture, and social values. The research aims to analyze the causes of conflicts, resolution patterns, and the contributions of socio-cultural approaches to creating effective and sustainable solutions. Employing a qualitative approach, the study utilizes case studies involving semi-structured interviews, participatory observations, and document analysis. The findings reveal that social conflicts in HKI are often triggered by imbalances in social structures, gender roles, and the influence of local traditions that diverge from formal legal norms. The sociological approach provides insights into interaction patterns and social mediation, while the anthropological approach highlights the importance of cultural values in conflict resolution processes. The study's implications emphasize the necessity of integrating Islamic legal principles of justice with local traditions to foster conflict resolution that is harmonious and socially relevant.